Correlation between Mother's Behavior in Providing Early Complementary Feeding with the Incidence of Diarrhea - Nabila, Intan; Hananti, Freni Susilo; Abiddin, Andi Hayyun; Martiningsih, Wiwin; ACOB, Joel Rey U. (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
Babies are golden periods because in this period the babies will experience very significant. One of the influences on a baby's growth and development is providing nutrients to the baby appropriately according to his age, one of which is a complementary food. The purpose study was to determine the relationship between maternal behavior in early breastfeeding and the incidence of diarrhea in infants, in addition to identify mothers' breastfeeding behavior, the type of complementary food given, and the incidence of diarrhea in early breastfeeding. The method used a Traditional Study Review design and used the keywords